Social Protection Policies in Venezuela: between the illusion and the reality of the bolivarian socialism of the XXI century - Sáez González, Raquel; Vargas Acosta, Eglée (Journal of the University of Zulia, 2022)
The article analyzes the social policies that characterize the daily life of Venezuelans between 2003 and 2022; particularly the state guidelines of the social missions were studied. Methodologically, a descriptive-analytical and documentary study of the Venezuelan State policies was carried out based on the social action plans and programs designed for the protection of the population, in contrast with the results of the Living Conditions Survey, 2021. The findings point out that the Social Missions lost coverage since 2017; the Coronavirus pandemic and the gasoline shortage gave way to a new social policy based on direct transfers and distribution of food bags. In conclusion, the missions and large social missions implemented by the national government to provide the greatest welfare to the Venezuelan population have disappeared in the face of waste, corruption and lack of investment, monitoring and follow-up of the same.